A Mathematical Blended Learning Model for University Students - Miniyarovna Ahmerova, Nuriya; Leontievna Fatykhova, Alevtina; Murzabayevna Suleymanova, Fanya; Nikolaevna Russu, Olga; Irekovna Kokhanovskaya, Indira; ., . (International Journal of Engineering and Technology, 2018)
The article aims to develop a model for assessing the quality of blended learning for university students. Different viewpoints on blended learning and the quality of learning are summarized and systematized. A model and method for assessing the quality of blended learning are presented. Approaches are developed for obtaining estimates of the quality of learning based on a priori and a posteriori assessment methods.Â Â Â